Clinical implications of reduced susceptibility to fluoroquinolones in paediatric Shigella sonnei and Shigella flexneri infections - Thompson, C; Thieu, N; Vinh, P; Duc, A; Wolbers, M; Vinh, H; Campbell, J; Ngoc, D; Hoang, N; Thanh, T; The, H; Nguyen, T; et al. (Oxford University Press, 2015)
Objectives: We aimed to quantify the impact of fluoroquinolone resistance on the clinical outcome of paediatric shigellosis patients treated with fluoroquinolones in southern Vietnam. Such information is important to inform therapeutic management for infections caused by this increasingly drug-resistant pathogen, responsible for high morbidity and mortality in young children globally. Methods: Clinical information and bacterial isolates were derived from a randomized controlled trial comparing gatifloxacin with ciprofloxacin for the treatment of paediatric shigellosis. Time–kill experiments were performed to evaluate the impact of MIC on the in vitro growth of Shigella and Cox regression modelling was used to compare clinical outcome between treatments and Shigella species. Results: Shigella flexneri patients treated with gatifloxacin had significantly worse outcomes than those treated with ciprofloxacin. However, the MICs of fluoroquinolones were not significantly associated with poorer outcome. The presence of S83L and A87T mutations in the gyrA gene significantly increased MICs of fluoroquinolones. Finally, elevated MICs and the presence of the qnrS gene allowed Shigella to replicate efficiently in vitro in high concentrations of ciprofloxacin. Conclusions: We found that below the CLSI breakpoint, there was no association between MIC and clinical outcome in paediatric shigellosis infections. However, S. flexneri patients had worse clinical outcomes when treated with gatifloxacin in this study regardless of MIC. Additionally, Shigella harbouring the qnrS gene are able to replicate efficiently in high concentrations of ciprofloxacin and we hypothesize that such strains possess a competitive advantage against fluoroquinolone-susceptible strains due to enhanced shedding and transmission.